A response for substance and harm reduction in Pacific Island countries and territories. Issue 1 (December 2015) - Power, Robert; Schmich, Lucina; Nosa, Vili
Abstract The Pacific is characterised as a region for the purposes of many international interventions and assistance programmes. Representatives of Pacific States participate in regional fora to build a strategic and unified approach to development. Regionally, bilateral trade agreements impact upon strategies to regulate alcohol imports. Policing and customs initiatives are increasingly supporting prevention of illicit drug production and trafficking, and model laws have been proposed to achieve consistency in enforcement. The aim of this commentary is to provide a response for policies using the case of alcohol and other drug research in the Pacific Islands Countries Territories. This commentary undertook a review of the current literature for regional developments for alcohol and other drug use in the Pacific Island Countries Territories region. A total of 14 articles were used in this article. The publication date for the articles used in this review ranged from 1997 to 2011. The findings of the review found that there should be a co-ordinated approach for adopting alcohol and other drug approaches. Furthermore, there should be a co-ordinated regional response with the inclusion of targeted domestic programming that will meet the needs for the Pacific Island countries and territories. Countries in the Pacific Island territories are characterised by varying degrees of political stability. Without stable government and democratic process, it is likely to remain difficult to develop consistent and effective legislation and policy for implementation of successful alcohol and other drug programmes. We found that there is a lack of robust and current data for alcohol and other drugs in Pacific Island countries and territories. Further research funding is needed to build the limited knowledge of alcohol and other drug substance use.